2019
DOI: 10.3390/nu11112654
|View full text |Cite
|
Sign up to set email alerts
|

Obesity- and Lipid-Related Parameters in the Identification of Older Adults with a High Risk of Prediabetes According to the American Diabetes Association: An Analysis of the 2015 Health, Well-Being, and Aging Study

Abstract: This study evaluated the predictive ability of 11 obesity- and lipid-related parameters, including body mass index (BMI), waist circumference (WC), waist-to-height ratio (WtHR), body roundness index (BRI), “A” body-shape index (ABSI), conicity index (C), visceral adiposity index (VAI), triglyceride-to-glucose fasting index (TyG), triglyceride-to-glucose fasting related to BMI (TyG-BMI), triglyceride-to-glucose fasting related to WC (TyG-WC), and triglyceride-to-glucose fasting related to WtHR (TyG-WtHR), to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 42 publications
3
55
1
Order By: Relevance
“…More importantly, previous cohort studies showed a positive relationship between high levels of the TyG index and the risk of incident diabetes [17][18][19][20], but the positive association disappeared at low levels of the TyG index [17,18,20]. This trend suggested a nonlinear association which had never been well characterized in previous studies.…”
Section: Background/introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…More importantly, previous cohort studies showed a positive relationship between high levels of the TyG index and the risk of incident diabetes [17][18][19][20], but the positive association disappeared at low levels of the TyG index [17,18,20]. This trend suggested a nonlinear association which had never been well characterized in previous studies.…”
Section: Background/introductionmentioning
confidence: 80%
“…The TyG index was suggested to be considered as a screening tool for identifying people at a high risk of T2DM in clinical practice [18]. Although studies on the TyG index as a risk of T2DM have been conducted in Singapore, Korean, Thailand, and the white European population [17][18][19][20], no data on the Japanese population are currently available.…”
Section: Background/introductionmentioning
confidence: 99%
“…The data for this secondary cross-sectional study were obtained from the Health and Well-being and Aging Survey in Colombia 2015 (SABE, from initials in Spanish: Salud, Bienestar y Envejecimiento, 2015), a multicenter project conducted from 2014 to 2015 by (in Spanish: Ministerio de Salud y la Protección Social de Colombia) [27]. The study included the Colombian population aged ≥60 years, and the indicators were disaggregated by age ranges, sex, ethnicity, and socioeconomic level.…”
Section: Study Design and Sample Populationmentioning
confidence: 99%
“…Moreover, the increased rate of MetS in low-incomed countries is dramatic 3. MetS is regarded as a risk factor for the development of type 2 diabetes mellitus (T2DM),4 cardiovascular disease,5 stroke,6 polycystic ovary syndrome, non-alcoholic steatohepatitis7 and cancer,8 which may all lead to mortality 9. MetS pandemic may cause heavy social and economic burden.…”
Section: Introductionmentioning
confidence: 99%